Effect of Mayer’s Modality Principle of Multimedia Design on Secondary School Students' Performance in Biology in Rivers State - Agbarakwe, Harriet Akudo; Ossai-Chidi, Amarachi Genevive (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2025)
This study examined the effect of Mayer’s modality principle of multimedia design on secondary school students' performance in Biology in Rivers State, Nigeria. The Modality principle suggests that students learn better when information is presented in both visual and auditory formats, rather than relying solely on text-based information. Three objectives and three research questions guided the study. A pre-test, post-test quasi-experimental design was adopted for the study. A sample size of 100 secondary school students participated in the study, divided into an experimental group (52 students) that received multimedia instruction based on the Modality principle, and a control group (48 students) that received traditional text-based instruction. Mean and standard deviation were used to answer research questions, while ANCOVA was used to test the hypothesis at a significance level of 0.5. The findings show that students who learned with multimedia designs aligned with the Modality principle had a higher mean performance score compared to those taught with the text-based principle. The study concludes that applying Mayer’s Modality principle in multimedia design can enhance students' academic performance in secondary school, Rivers State. It was recommended amongst others that teachers should receive training on Mayer’s Modality principle to effectively design lessons that reduce cognitive overload and improve engagement.